The intellectual core and structure of international business strategies (IBS): A co-citation analysis. Issue 3 (23rd August 2019) - Bhattacharyya, Som Sekhar; Verma, Surabhi
Abstract : Purpose: International Business Strategies (IBS) literature deliberated on the strategic planning and strategy implementation of home country firms in foreign markets. IBS had become a very potent growth strategy for firms. IBS as a body of knowledge had become substantial in the last few decades of research. To this end, and as a complex field of study, this paper aims to conceptually map this IBS literature. Hence, the purpose of this paper is to present a visual mapping of intellectual structure in two dimensions and to identify the subfields of IBS through co-citation analysis. Design/methodology/approach: All the citation documents were included in the Web of Knowledge (WoK) database between the years 1993 and 2018. For the multivariate analysis, this study applied a sequence of statistical analyses including factor analysis, multidimensional scaling and cluster analysis. Through these techniques, this research study tried to summarize the condition and status of IBS research by classifying the IBS literature into four categories. Findings: IBS literature has been classified into four categories, namely, evolutionary aspects of IBS; firm strategic objectives and IBS; institutional theory and IBS in emerging economies; and foreign market entry strategies for internationalization. Research limitations/implications: Based upon the basis of the analysis of extant research in IBS, the current and future extension research topics have been presented. This would help future researchers to understand the white spots for undertaking research in future. Originality/value: This was one of the very first studies that mapped the International Business Strategy literature and categorized IBS literature.